NUTRIENT UPTAKE STUDIES IN MACHINE TRANSPLANTED RICE (Oryza sativa L.) AS INFLUENCED BY NITROGEN LEVELS AND SPLIT SCHEDULES - and A. MADHAVI, GHANSHAM PAYMAN, P. RAGHU RAMI REDDY, A SRINIVAS, S. NARENDAR REDDY (The Journal of Research, PJTSAU, 2017)
An experiment was conducted during kharif seasons of 2014 and 2015 at Agricultural Research Institute, Hyderabad to optimize the nitrogen levels and split schedules on yield, nutrient uptake and nitrogen use efficiency. The experiment was laid out in a split plot design where three nitrogen levels were kept in main plot and three split schedules in sub plot with three replications using variety BPT 5204. Highest grain and straw yield (6119 and 8598 kg ha-1), total NPK uptake (144.2, 35.0 and 141.2 kg ha-1) and PK partial factor productivity (102.0 and 150.9 kg grain kg-1 NP) was recorded with application of 200 kg N ha-1and was at par with application of 160 kg N ha-1, except for straw yield and N Pfp. Partial factor productivity for N was inversely related to nitrogen application levels but positive for phosphorus and potassium. Three equal split schedules recorded maximum grain and straw yield (6028 and 8184 kg ha-1), total NPK uptake (136.4, 35.6 and 139.2 kg ha- 1) and partial factor productivity (39.1, 100.5 and 150.2 kg grain kg-1 NPK). The results indicated that the use of 160 kg N ha- 1 applied in three equal splits at initial tillering, active tillering and panicle initiation had better performance and thus can be adopted for higher productivity in machine transplanted rice.